Study Of The Effect Of Addition Of Butone Granular Asphalt 5/20 On Marshall Characteristics Of Hot Mix Asphalt AC-WC - M. Iqbal Zaihan Batubara (IHSA Institute, 2021)
As buton product that is currently being developed is Asbuton type BGA or called Buton Granular Asphalt which has bitumen content between 20-25% (Puslitbang Prasarana Transport Dep.PU, 2005). BGA has been used in several locations but its use is considered not optimal, therefore the authors want to examine how the effect of variations in the level of addition of asbuton material on the performance of asphalt mixtures. In this study, testing was carried out in stages, starting with material testing consisting of aggregate testing (coarse, fine, filler), as well as asphalt property testing and BGA material testing. Then a mixture of Marshall test objects will be made to be tested. The mixed test method used is the Marshall method which will then produce parameter values ​​in the form of VFB (Void Filled Bitumen), Stability, Residual Stability, VIM (Void in Mix), VMA (Void Mineral Aggregate), flow, and MQ (Marshall Quotionent). The purpose of this study was to determine the effect of adding variations in the use of BGA type 5/20 materials, namely 0%, 3% and 5% on Marshall characteristics of AC-WC hot asphalt mixture using the 2010 Binamarga Specification Revision 3. The results showed that the addition of Asbuton Item 5/20 significantly increased the value of stability, residual stability and MQ along with increasing levels of asbuton used, but did not significantly affect the value of VMA, VFB and Flow and concluded that the use of Asbuton BGA with a level of 3% has produced optimal results.